Davao Sack Traders - Santos, Suzzette Marie B.; Soledad, Miguel D.; Durana, Annalee D. (Davao City School of Management, University of the Philippines Mindanao, 2007)
The Davao Sack Traders is a family owned enterprise that has undergone exponential growth over the last 20 years. It has opened a number of branches in Mindanao and has expanded its market and supplier base. This growth has not proven to be very successful as most of the branches closed down due to bankruptcy. It was found out that although there are opportunities that called for expansion, the threats and other weaknesses were overlooked. The study has conducted an internal and external audit to identify the different factors that affect the operations of the business. Some of the external factors include positive economic indicators, the decline of mining outputs, the improvements in agriculture and the threats depleting resources. Internal factors such as low storage costs and low employee turn over as well as marketing efficiency and capital position were identified. A number of strategies were formulated to overcome the threats and weaknesses at the same time maximize opportunities and strengths. These were categorized into five grand strategic options: Cost leadership, Product leadership, Market development, Liquidation and Strategic alliances. The attractiveness of each of these strategies is determined through the Quantitative Strategic Planning Matrix. Davao Sack Traders aims to undertake market development as its primary strategy to increase its sales by 20% annually. This is to be simultaneously implemented with cost leadership strategy to reduce annual operations costs by 10%. These strategies are expected to increase annual net income by at least 33%.
Thesis, Graduate(Master in Management)--University of the Philippines Mindanao, December 2007.